Kakintalan mga mabilisang impresyon ng ilang kabataan at gurong Bulakeño - De Veyra, Vicente Ignacio Soria (Bocaue, Bulacan Bocaue Arts & Cultural Society, 2006)
A collection of literary works by the Bocaue Arts and Cultural Society.
In Tagalog, and some articles in English.
Keywords: Tagalog poetry; Tagalog essays